Evaluasi Perkerasan Kaku Menggunakan Metode Pavement Condition Index pada Proyek Peningkatan Jalan - Emka Albertta Sitepu; Subrata Aditama K.A. Uda; Okta Meilawaty (Jurnal Konstruksi, 2026)
Evaluation of rigid pavement conditions is very important to ensure the structural and functional performance of roads, particularly in national strategic road projects. Previous research by Rizaldi, Hermansyah, and Mawardin (2023) using the Pavement Condition Index (PCI) method on the Q-R4 section of MUTIP 1 Mandalika Road obtained a PCI score of 90.875, which was categorized as very good. The identified damages consisted of linear cracking, corner cracking, joint filler deterioration, pumping, and mortar and aggregate wear. However, the previous study focused on the general surface condition of the pavement, while the analysis of initial damage to the lean concrete layer remained limited. This study aims to assess the condition of rigid pavement in the Precinct Core and Sumbu Tripraja Road Improvement Project in East Kalimantan using the PCI method. Data were obtained through visual observations, project documentation, and measurements of damage on the lean concrete layer. The results indicate damage in the form of longitudinal and transverse cracks (linear cracks) with a total damaged area of 0.11855 m². The Density value was 0.172346 percent, the Deduct Value was 7.2436, and the Corrected Deduct Value was also 7.2436, resulting in a PCI value of 92.7564, which falls into the very good category. These findings indicate that the pavement condition is excellent and confirm that the PCI method is effective as a basis for evaluating pavement quality and implementing preventive maintenance strategies for rigid pavements.